Hypotensive Anaesthesia during Spine Surgery – A Comparison between Dexmedetomidine and Magnesium Sulphate - Kabir, Ahsanul; Azad, Abul Kalam; Rustom, A T M A; Akter, Suraya; Mahmood, Md Hasan; Ashraf, Rashed; Shah, Muinul Islam; Islam, Md Mujahidul; Jahan, Aziza (Community Based Medical Journal, 2023)
A good visualization of the surgical field can be achieved by controlled hypotension with various hypotensive agents. Both dexmedetomidine and Magnesium Sulphate (MgSO4) has powerful analgesic effect and can induce hypotension during surgery. This study is aimed to compare the efficacy of Dexmedetomidine with Magnesium Sulphate in controlled hypotension during spine surgery. This randomized, prospective study was carried out in anesthesiology department of Combined Military Hospital, Dhaka for six-months of period following ethical approval. Total 60 patients, scheduled for spine surgery under GA were included in this study and randomly divided into Group D (Dexmedetomidine, n=30) and Group M (Magnesium sulfate, n=30). Informed written consent was taken from each subject. In every 15 mins, heart rate, systolic & diastolic blood pressure, mean arterial pressure (MAP) are assessed and the surgical field was assessed by the Boezaart surgical field bleeding score. Data were collected in separated case-record form and analyzed by the SPSS 24. Demographic characteristics were similar across the two groups in terms of age, sex, BMI, ASA grading, pre-operative systolic and diastolic blood pressure (p>0.05). Group D had higher mean duration of controlled hypotension (102.50±33.44 vs 85.33±20.25 minutes, p=0.02) and lower mean time to achieve target MAP (34.50±22.68 vs 46.00±10.37 minutes, p=0.016) than Group M. MAP was significantly lower for Group D patients than the Group M patients with time (p<0.05). Boezaart surgical field bleeding score was also significantly lower in Group D compared to Group M (p<0.05). In this study Dexmedetomidine is found more effective than Magnesium Sulphate in achieving controlled hypotension during spine surgery. Better haemodynamic stability is also found in Group D in comparison to Group M. CBMJ 2023 July: vol. 12 no. 02 P: 171-182